STRATEGIES TO MITIGATERISKS TO SMALL AND MEDIUM INDUSTRY’S ECONOMY DURING PANDEMIC COVID-19 - Burhanuddin Mohd Aboobaider (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
-